Neuroprotective Effects of Bone Marrow Stromal Cell Transplantation in Combination With Treadmill Exercise Following Traumatic Brain Injury - Mal Soon Shin; Hun Kyung Park; Tae Woon Kim; Eun Sang Ji; Jae Min Lee; Han Sung Choi; Mi Ye Kim; Young Pyo Kim (International Neurourology Journal, 2016)
Purpose: Traumatic brain injury (TBI) causes cognitive impairments, motor deficits, and neuropsychiatric/behavioral deficits problems. Transplantation of bone marrow stromal cells (BMSCs) facilitates functional recovery from brain insults. Treadmill exercise increases neurogenesis and inhibits apoptosis. In this study, we investigated the effects of BMSC transplantation in combination with treadmill exercise on memory function, by evaluating its effect on neurogenesis and apoptosis in the hippocampus following TBI. Methods: TBI was induced using an electromagnetic-controlled cortical impact device. BMSCs were transplanted into both sides of traumatic scar region 1 week after TBI induction. One week after transplantation of BMSCs, the rats in the exercise groups were trained to run on a treadmill for 30 minutes once daily for 28 days. Step-down avoidance task and radial 8-arm maze test were conducted. Levels of 5-bromo-2ʹ-deoxyuridine and caspase-3 were evaluated using immunohistochemistry. Western blot was used to evaluate the expression of brain-derived neurotrophic factor (BDNF), tyrosine kinase B (TrkB), total-extracellular signal-regulated kinase 1 and 2 (t-ERK1/2), phosphorylated-ERK1/2 (p-ERK1/2), Bcl-2, and Bax. Results: TBI deteriorated memory function, suppressed neurogenesis, and accelerated apoptosis in the hippocampus. Treadmill exercise and BMSC transplantation independently improved memory function by increasing neurogenesis with suppression of apoptosis through the BDNF-ERK pathway in the TBI-induced rats. Combination of BMSC transplantation with treadmill exercise showed additional enhancement of neurogenesis and suppression of apoptosis in the hippocampus. Conclusions: The present study shows that treadmill exercise may aid the therapeutic effect of BMSC transplantation on TBI in rats.